Impact of Different Importation Policies Scenarios on Beef Industry in Peninsular Malaysia - Mark Buda; Zainalabidin Mohamed (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
The supply side of beef industry has not responded well to the rising demand for beef. This industry is still highly dependent on imported beef and feeder cattle for beef production to meet the local demand. The objective of this study is to analyse the impacts of different importation policy scenarios on beef industry in Peninsular Malaysia. A simulation model that based on estimated market model is used to analyse the policy. The findings imply that the number of import cattle for breeding (ICTB) should be maintained, while import of cattle for slaughter or feeder cattle should be increased by 20%. This will improve beef self-sufficiency level while stabilizing beef retail price.